Agricultural waste-based magnetic biochar produced via hydrothermal route for petroleum spills adsorption - Dessy Ariyanti; I Nyoman Widiasa; Marissa Widiyanti; Dina Lesdantina; Wei Gao (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Oil spills are one of the marine pollution events triggered by the results of tanker operations (air ballast), ship repairs and maintenance (docking), mid-ocean loading and unloading terminals, air bilge (drainage of water, oil, and engine-processed lubricants), ship scrapping, and the most common accidents/collisions of tankers. The impacts vary from the death of marine organisms, especially fish, changes in reproduction and behavior of organisms, plankton contamination, fish migration, as well as ecosystem damage, and economic loss. Bio-based absorbents such as biochar can be an environmentally friendly alternative to chemical sorbents that works to adsorb oil spills faster. In this study, the effectiveness of magnetic biochar in oil spill removal was investigated. It also includes the synthesisation of magnetic biochar from agricultural waste (bagasse, rice husks, and sawdust) using the hydrothermal method at a temperature of 200°C. Hydrothermal carbonization is considered a cost-effective method for biochar production because the process can be carried out at low temperatures around 180°- 250°C. Biochar characterization was carried out with a Scanning Electron Microscope and Energy Dispersive X-Ray (SEM-EDX), Fourier Transform Infrared Spectroscopy (FTIR), and X-Ray Diffraction (XRD). The Brunauer, Emmett, and Teller (BET) and Barrett–Joyner–Halenda (BJH) were used to analyse the surface area and pore size distribution. Based on the results of the SEM-EDX analysis, only biochar was made from rice husk and sugarcane bagasse which contained Fe elements, as a result of the FeCl3.6H2O reaction. This condition is also proven by the presence of the FeO on both samples based on FTIR. The three synthesized biochar are amorphous and categorized as mesopores due to pore size around 15 to 16 nm, which can absorb petroleum spills with a percentage of 81% for sugarcane bagasse-based biochar, 84% for rice husk-based biochar, and 70% for sawdust-based biochar. Biochar from rice husk has excellent adsorption effectiveness with an adsorption capacity of 0.21 g/g in 60 min due to its large functional group area and the excellent attachment of magnetic compound into the biochar surface to form magnetic biochar.